1999
DOI: 10.1117/12.350198
|View full text |Cite
|
Sign up to set email alerts
|

Aerial image contrast using interferometric lithography: effect on line-edge roughness

Abstract: Interferometric lithography affords the unique ability to independently control dose, pitch and aerial image contrast during photolithographic exposure. In this report, we describe the use of a deep-UV interferometric lithography exposure tool to study the impact of aerial image contrast on resist imaging properties. A wide range of high resolution resist materials was surveyed, including positive-and negative-tone systems, chemically amplified and conventional diazonaphthoquinone imaging chemistries, and aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Due to the large amount of data needed for strong statistical conclusions, only one photoresist is examined. As Sanchez et al have shown, each photoresist acts differently to contrast variations (8). However, UVII-HS is an adequate choice since it has many attributes in common with other DUV photoresists.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…Due to the large amount of data needed for strong statistical conclusions, only one photoresist is examined. As Sanchez et al have shown, each photoresist acts differently to contrast variations (8). However, UVII-HS is an adequate choice since it has many attributes in common with other DUV photoresists.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…A detailed analysis of the effect of aerial image contrast was performed in which the image slope at the feature edge was varied and the resulting change in LER of several resists was determined. 2 It was noted that LER increased as the AIC decreased. But perhaps more importantly, it was determined that different resists have unique responses to changes in AIC, suggesting that the resist material's composition plays a major role in contributing to LER.…”
Section: Introductionmentioning
confidence: 98%
“…It can originate from a myriad of factors such as the photon or chemical shot noise, molecular stacking, development process, and low image contrast [1,[13][14][15][16][17][18][19][20][21]. Recently, mask roughness gained significant attention as one of the contributors to the wafer LER [2-9, 22, 23].…”
Section: Introductionmentioning
confidence: 99%